Spatiotemporal behaviour of the urban multi-attraction tourist: does distance travelled from country of origin make a difference? - Ana Maria Caldeira; Elisabeth Kastenholz (Tourism & Management Studies)
The way tourists move in space and time is part of their travel experience while at the same time moulding it. In the urban context, tourists usually include multiple attractions on their intradestination itineraries. Understanding tourists’ spatiotemporal behaviour may help improve the quality of their experience as well as provide useful information to the management of attractions and destination. Nevertheless, tourists’ spatiotemporal behaviour is a complex phenomenon, influenced by numerous factors related to both destination and tourists. Distance travelled from country of origin has been empirically found as one of these factors influencing tourist spatiotemporal behaviour. Visitors from more distant residential locations invest more time and money in their trip; therefore, variety/multiple benefit seeking, risk and uncertainty reduction and economic rationalization may impact their time-space activity. However, there has been no research examining the impact of distance travelled from country of origin specifically on tourist spatiotemporal behaviour in an urban setting. This article fills this gap both theoretically and empirically, through a dual analysis of a time-space GPS tracking study and a survey, conducted among tourists (n=413) staying at 10 different hotels in Lisbon. Hypothesis testing allowed the identification of statistically significant differences between long-haulers and shorthaulers in their spatiotemporal behaviour when visiting this urban destination.